Development and fabrication of moveable automatic fish feeder / Mohamad Danial Syahmi Mohamad Aziz - Mohamad Aziz, Mohamad Danial Syahmi (2023)
Unlike other pets that can move freely on the surface, fish only can survive for several minutes outside of water. Because of that, the source of food for them is limited. The time when they eat is the time when their owner feeds them. That’s why people start to buy an automatic fish feeder at the market, so the device can assist them in feeding their fish even if they are away far from home for days. However, the device still has disadvantage, making people lose interest in raising variable types of fish as pets. This project aims to design a new type of automatic fish feeder and develop an ARDUINO system with the function of movement. The selection process will be made to choose the most pleasing design for the product. After that, an isometric view of the product will be created using state-of-art SolidWorks 2018. The designed product will work on electricity and will consist of simple fabrication as a proof of concept. Analytical and finite element analysis of the critical parts shall be carried out. Having this product shall assist the user to feed the fish kept in different small aquariums every day. As a result, the production of this product can run smoothly and successfully achieve the objectives